1954
DOI: 10.1002/ange.19540661104
|View full text |Cite
|
Sign up to set email alerts
|

Polarographische Kennzeichnung organischer Strukturtypen. I. Mitteilung: Unterscheidung zwischen Indolen, Indoleninen und α‐Methylen‐dihydroindolen

Abstract: B2HZ-NC Die Polarographie als Test auf die Strukturen 1-111 hat sich in unseren Untersuchungen an S t r y c h n o s -A lk a l o i d e n bereits bewahrt; hieriiber wird anderweitig berlchtet. Das Verfahren verspricht, besonders da es sich um eine ausgesprochene Mikromethode handelt, eine entsprechende Charakterisierung auch von Calebassen-Curare3) zu ernloglichen. 293

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1956
1956
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Polarographic studies are reported for -pyrrole aldehyde (54) and of-methylenedihydroindole (97). The reduction reported in the latter paper for V-vinylcarbazole may be due to peroxides.…”
Section: Nitrogen-containing Heterocyclic Compoundsmentioning
confidence: 89%
“…Polarographic studies are reported for -pyrrole aldehyde (54) and of-methylenedihydroindole (97). The reduction reported in the latter paper for V-vinylcarbazole may be due to peroxides.…”
Section: Nitrogen-containing Heterocyclic Compoundsmentioning
confidence: 89%
“…The electrochemical reduction potential of tryptophan has not been determined. However, from the values of corresponding organic molecules, the reduction potential of tryptophan in polar solutions can be estimated to lie between l .7 and -2.0 eV (Ender et al, 1954;Volke, 1963). Besides, tryptophan M252 could accelerate the electron-transfer via the so-called superexchange mechanism (Michel-Beyerle et al, 1988 ;Halpern and Orgel, 1960;McConnell, 1961 ;Larsson, 1981 ;Miller and Beitz, 1981;Beratan et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…sphaeroides shows a hydrogen bond from threonine M222 to the quionone QA and not to the tryptophan M252. However, another previously published structure (Allen et al, 1988) and the recent high resolution (0.23 nm) structure (Buchanan et al, 1993;Ermler et al, 1992; H. Michel, unpublished results) indicate that the hydrogen bridge is di- Fig. 1.…”
mentioning
confidence: 89%
See 1 more Smart Citation